Motor and Nonmotor Features of Carriers of the p.A53T Alpha‐Synuclein Mutation: A Longitudinal Study. Issue 8 (29th March 2016) - Papadimitriou, Dimitra; Antonelou, Roubina; Miligkos, Michael; Maniati, Matina; Papagiannakis, Nikolaos; Bostantjopoulou, Sevasti; Leonardos, Athannassios; Koros, Christos; Simitsi, Athina; Papageorgiou, Sokratis G.; Kapaki, Elisabeth; Alcalay, Roy N.; et al.
ABSTRACT: Background: G209A SNCA mutation carriers represent an important group of genetic PD. We describe motor and nonmotor features of G209A SNCA mutation carriers. Methods: Longitudinal clinical assessments over 2 years were collected in 22 symptomatic and 8 asymptomatic G209A SNCA mutation carriers. Motor and nonmotor rating scales were administered. Correlations were performed between clinical variables and disease duration or age. Penetrance was calculated using Kaplan‐Meier survival curves. Results: Asymptomatic carriers did not manifest clear premotor symptoms, but symptomatic carriers often reported that olfactory dysfunction and rapid eye movement sleep behavior disorder preceded motor symptoms. Prominent motor decline and deterioration of autonomic and cognitive function occurred at follow‐up; such nonmotor features correlated with disease duration, but not age. Disease penetrance was estimated at around 90%. Conclusions: This study may help to inform clinical trials and provide the basis for studies of disease modifiers in genetic synucleinopathy cohorts. © 2016 International Parkinson and Movement Disorder Society